2013
DOI: 10.1517/17425247.2013.808184
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of antibody-based therapeutic and imaging agents to CNS tumors: crossing the blood–brain barrier divide

Abstract: Introduction Brain tumors are inherently difficult to treat in large part due to the cellular blood-brain barriers (BBB) that limit the delivery of therapeutics to the tumor tissue from the systemic circulation. Virtually no large-molecules, including antibody-based proteins, can penetrate the BBB. With antibodies fast becoming attractive ligands for highly specific molecular targeting to tumor antigens, a variety of methods are being investigated to enhance the access of these agents to intracranial tumors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 135 publications
0
64
1
Order By: Relevance
“…Recent innovations in radiation therapy have improved precision, tumor definition with imaging, and radiation delivery through beam shaping. 24 In addition to its current utility, radiation therapy may play a role in selectively disrupting the BBB. Studies in both animals and humans have demonstrated that radiation therapy can induce focal BBB disruption with minimal effects on normal vasculature.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Recent innovations in radiation therapy have improved precision, tumor definition with imaging, and radiation delivery through beam shaping. 24 In addition to its current utility, radiation therapy may play a role in selectively disrupting the BBB. Studies in both animals and humans have demonstrated that radiation therapy can induce focal BBB disruption with minimal effects on normal vasculature.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Two notable examples include bradykinin analog RMP-7 and calcium-dependent potassium channels (KCa) [48]. RMP-7 is a bradykinin B2 receptor agonist with an increased half-life over bradykinin.…”
Section: Strategies For Cns Deliverymentioning
confidence: 99%
“…Tumor and brain tissue uptake limited by BBB [72]. Cationic Polymers EPR effect and/or targeting group (i.e., cationic moiety) [73].…”
Section: Antibody-dendrimer Conjugatesmentioning
confidence: 99%
“…The advantages of boron-mAb conjugates are their high T/N selectivity and T/B ratios. However, one limitation is that systemic administration of mAbs will result in poor brain tumor uptake due to their limited ability to cross the BBB [72].…”
Section: Antibody-dendrimer Conjugatesmentioning
confidence: 99%